Infertilization of dengue vector (Aedes aegypti) with Bromelin Solution and Extract From Ananas comosus - Isnawati, Isnawati; Muhammad Ir'fai; Ferry Kriswandana; Wanti Wanti; Muhammad Pahruddin; Ridha, Muhammad Rasyid (Jurnal Kesehatan Masyarakat, 2025)
Dengue fever remains a significant public health problem in the tropics, with Aedes aegypti as the primary vector. Insecticide resistance among mosquitoes has been increasing, so an environmentally friendly alternative approach with biolarvicides is needed. This study aimed to evaluate the effects of bromelain and pineapple (Ananas comosus) extracts on the reproductive parameters of Aedes aegypti. Experiments were conducted in a controlled laboratory, where mosquitoes were exposed to various concentrations (0% to 10%) of bromelain and pineapple extracts. The number of egg production, hatching rate, and lifespan of adult mosquitoes were measured. Our results showed Bromelain, especially at higher concentrations, significantly reduced egg production, hatching rate, and longevity compared to the control and pineapple extract. At 6% and 8% bromelain concentrations, egg production and hatchability were very low, and mosquito lifespan was reduced. Pineapple extract also showed an inhibitory effect on egg production, although less consistently than bromelain. The sugar solution used as a control produced more eggs and live longer. In conclusion, bromelain from Ananas comosus showed promising insecticidal potential by reducing mosquito fertility and longevity, indicating its utility as an alternative vector control strategy for managing dengue outbreaks.